Qualitative evaluation of antibiotic usage in pediatric patients - Hindra Irawan Satari; Agus Firmansyah; Theresia Theresia (Indonesian Pediatric Society, 2011)
Background Antibiotics are among the most commonly prescribed drug for pediatric patients. Inappropriate use of antibiotics can increase morbidity, mortality, patient cost and bacterial antibiotic resistence. Antibiotic uses can be evaluated quantitatively and qualitatively.Objective To qualitatively evaluate antibiotic use in patients using Gyssens algorithm.Methods We performed a descriptive, retrospective study of matient medicalÂ records of those admitted to the pediatric ward from January 1 â€“ June 30, 2009.Â Records were screened for patient antibiotic use, followed by qualitative evaluation using Gyssens algorithm on data from patient who received antibiotic treatment.Results We found 49.2% of subject were prescribed antibiotics. The majority of patients given antibiotics were aged 1 month - 1 year (39.3%). Antibiotic use was categorized by therapy type : empirical, prophylactic, or definitive. We found empirical therapy in 73% of cases, prophylactic in 8%, and definitive in 15%. Cefotaxime was the most common antibiotic used (25.1%), followed by ceftazidime (14%) and cotrimoxazole (1%). 39.6% of subjects were given antibiotics appropriately, while 48.3% were given inappropriately. In 3.3% of patients, antibiotics were given without indication and in 8.8% there was insufficient data.Conclusions Of hospitalized patients receiving antibiotic treatment at the Departement of Child Health, Cipto Mangunkusumo Hospital, 39.6% were given antibiotic appropriately, while 48.3% were given antibiotics inappropriately. Cefotaxime was the most commonly used, as well as most inappropriately given antibiotic.